Case Report: Severe Peripartum Cardiac Disease in Myotonic Dystrophy Type 1 - Besant, Georgia; Bourque, Pierre R.; Smith, Ian C.; Chih, Sharon; Lamacie, Mariana M.; Breiner, Ari; Zwicker, Jocelyn; Lochmüller, Hanns; Warman-Chardon, Jodi (Frontiers in Cardiovascular Medicine, 2022)
Background: Myotonic dystrophy type 1 (DM1) is a hereditary muscular dystrophy affecting ~2.1-14.3/100,000 adults. Cardiac manifestations of DM1 include conduction disorders and rarely cardiomyopathies. DM1 increases the risk of obstetric complications however little is known about the relationship between pregnancy and cardiomyopathy in DM1 due to disease rarity. Case: A 23-year-old with DM1 developed cardiomyopathy during pregnancy. Despite initial medical stabilisation, she subsequently developed multiple spontaneous coronary artery dissections postpartum, worsening cardiomyopathy and multiorgan failure. She died 5 months postpartum. Conclusion: Though cardiomyopathy and arterial dissection are both known complications of pregnancy, this case suggests individuals with myotonic dystrophy type 1 may be at heightened risk for cardiac disease during the peripartum period. Physicians caring for women with suspected or proven DM1 should offer counseling and be alerted to the risk of cardiac complications with pregnancy and in the peripartum period. Pregnant and peripartum women with DM1 are likely to benefit from more frequent assessments of cardiac function including echocardiograms and early institution of heart failure management protocols when symptoms of cardiomyopathy present.